Mapping policy preferences from texts statistical solutions for manifesto analysts - Volkens, Andrea; Bara, Judith; Budge, Ian; McDonald, Michael D. (Michael Dennis) 1951-; Klingemann, Hans-Dieter (Oxford University Press, 2014)
Policy targets and political preferences are summarised in documents such as party manifestos. This book describes how these can be analysed quantititavely, by counting sentences devoted to each policy area. The numbers form policy indicators which can be related to government actions and spending. This book discusses problems with such analyses.